2023
DOI: 10.1161/jaha.122.027693
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Overweight: Probing Causes, Consequences, and Novel Therapeutic Approaches Through the American Heart Association's Strategically Focused Research Network

Abstract: As the worldwide prevalence of overweight and obesity continues to rise, so too does the urgency to fully understand mediating mechanisms, to discover new targets for safe and effective therapeutic intervention, and to identify biomarkers to track obesity and the success of weight loss interventions. In 2016, the American Heart Association sought applications for a Strategically Focused Research Network (SFRN) on Obesity. In 2017, 4 centers were named, including Johns Hopkins University School of Medicine, New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Although behavioral and lifestyle modifications are the foundation of obesity management, they have not demonstrated reliable or sustained large weight loss (≥ 10% of total body weight) in the majority of people with obesity [8,[26][27][28]. Moreover, the pathophysiology of obesity involves complex interactions between biological, behavioral, and environmental factors, and hence, effective treatment for obesity often requires the addition of biological-based measures, such as bariatric surgery or pharmacotherapy to lifestyle [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although behavioral and lifestyle modifications are the foundation of obesity management, they have not demonstrated reliable or sustained large weight loss (≥ 10% of total body weight) in the majority of people with obesity [8,[26][27][28]. Moreover, the pathophysiology of obesity involves complex interactions between biological, behavioral, and environmental factors, and hence, effective treatment for obesity often requires the addition of biological-based measures, such as bariatric surgery or pharmacotherapy to lifestyle [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity activates inflammatory cells and causes diabetes due to insulin resistance [ 4 ]. Studies from the Multi-Ethnic Study of Atherosclerosis (MESA) and National Health and Nutrition Examination Survey (NHANES) found that obesity was associated with 30%–53 percent of new diabetes cases in the United States each year [ 5 ]. Additionally, obese people are almost three times more likely to develop type 2 diabetes than non-obese people [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…O besity is an unhealthy condition associated with cardiovascular risk factors such as hypertension, type 2 diabetes, dyslipidaemia, metabolic syndrome, and sleep disorders representing a dramatically growing burden for the healthcare system worldwide [1,2]. A large body of evidence has accumulated in recent decades on the link between obesity and increased risk of nonfatal and fatal cardiovascular events, including heart failure, atrial fibrillation, coronary artery disease, and stroke [3][4][5].…”
Section: Introductionmentioning
confidence: 99%